Preliminary pharmacological screening of Eulophia herbacea lindl. tubers extract for anti-inflammatory potential in experimental animals (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Aim of current study was to screen various extracts of Eulophia herbacea tubers for anti-inflammatory effect on carrageenan induced paw oedema (acute models) and Cotton pellet granuloma model (chronic model) in experimental animals. Anti-inflammatory effects were observed by percent reduction in paw edema, assessment of granuloma weight and proinflammatory cytokine level. Diclofenac sodium (10 mg/kg bw) was utilized as standard drug for comparison. Study observation confirmed that ethanol extract (EEH) and aqueous extracts of Eulophia herbacea (AEH) tubers were reduces higher percentage of edema inhibition and comparable to the standard group. Granuloma weight of control group was increases after implantation of sterile pellet and was measured on after 8th day. A substantial (P<0.05) reduction in weight of granuloma was witnessed in EEH and AEH groups of animals at dose dependent manner. Level of proinflammatory markers (TNF-α, IL-6 and PGE2) were decreases significantly when compared granuloma tissue of control group of animals. In conclusion, ethanol and aqueous extracts of Eulophia herbacea tubers may reduce proliferative phase as proven by decrease in granuloma weight. Flavonoids present in ethanol extract and polysaccharides present in aqueous extract may be responsible for anti-inflammatory potential of Eulophia herbacea tubers.